The Development of Cash Waqf in Indonesia and Its Role in Advancing Education and Economic Empowerment - Suratno, Suratno (Sharia Faculty Islamic Economic Law Study Department, 2025)
As time progresses, human needs and problems become increasingly complex. Cash waqf presents a strategic solution to these challenges, particularly in Indonesia, where the practice is relatively new. The rapid development of cash waqf in Indonesia is expected to contribute to improving the nation's welfare. Currently, many problems remain, such as the difficulty of accessing education for children in remote or poor areas, and the lack of adequate school facilities and infrastructure. The Indonesian economy also faces challenges such as low growth, high poverty, unemployment, and food issues. Cash waqf has significant potential to address these issues if managed optimally. This qualitative research aims to examine the development of cash waqf in Indonesia and its role in advancing education and the economy. The study results show that cash waqf became widely known in Indonesia following the 2012 fatwa from the National Sharia Council (DSN MUI), and its popularity continues to grow. In the field of education, cash waqf plays a significant role through material support for the advancement of educational institutions. In the economic sector, cash waqf has proven vital for reducing poverty, empowering the community's economy, and providing business capital for MSMEs.